Kepemimpinan Kepala Madrasah Berbasis Islami dalam Menciptakan Karakter Peserta Didik di Madrasah Ibtidiyah - Novita Sari (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study was to determine the influence of Islamic-based Madrasah leadership in creating the character of students at MTs Negeri 2 Deli Serdang. This research method is descriptive. The results showed that the teachers of MTS Negeri 2 Deli Serdang in their leadership showed a religious work ethic. such as cultivating a handshake and welcoming the arrival of residents at MTsN Negeri 2 Deli Serdang. This is done every day before the pandemic period, but at this time it is done once a week and we are also not allowed to shake hands just give greetings by applying 5S. The strategies for implementing the leadership of the madrasa principal to students in creating student character are by motivating, character, and student achievement, especially at MTs Negeri 2 Deli Serdang. In conclusion, the leadership of the Madrasah Principal has an effect on character development in the school environment that involves teaching staff and students Keywords: Islamic, Leadership, Character of Students